Membangun Kesadaran Siswa Kelas VI SD Negeri 1 Sumber Tentang Hak Dan Batasan Tubuh Melalui Kegiatan Penyuluhan - Indry Novita Sari; Asih Wahyuningsih; Haerul Nisa; Febi Andriyani; Hety Mariyanah; Dewanti Amaranggana Wajraprakara (Mathematics Education Study Program, 2025)
Sexual violence against children is a significant challenge in child protection in Indonesia, particularly in the digital era that influences interaction patterns and child safety. This study aims to raise awareness among sixth-grade students at SDN 1 Sumber about body rights and personal boundaries through interactive educational programs. Using a descriptive qualitative approach, the research involved 50 students as subjects, utilizing observation, interviews, and documentation methods. The results indicate a significant improvement in students' understanding of body rights and personal boundaries after participating in the educational activities. Students became more confident in protecting themselves and reporting uncomfortable situations. This study highlights the importance of early education on body rights as a preventive measure against sexual violence and as a foundation for fostering self-protection awareness in children.